Effect of Low Dose Dopamine on Early Graft Function in Living Unrelated Kidney Donors - Hosseinzadeh, Hamzeh; Golzari, Samad; Abravesh, Mohammad; Mahmoodpoor, Ata; Aghamohammadi, Davood; Zomorrodi, Afshar; Hosseinzadeh, Parisa (Urology Journal, 2012)
Purpose: To evaluate the effect of low-dose dopamine administration on the early function of the kidney in unrelated kidney donors after transplantation. Materials and Methods: In this double-blinded clinical trial, 60 adult kidney donors and 60 recipients, younger than 50 years old, were studied. Donors and recipients were randomly divided into two groups; group 1 received dopamine 3 µg/kg/min and group 2 received similar regimen of placebo. During the first 3 days postoperatively, serum levels of urea and creatinine as well as urine output and early kidney function were compared between two groups. Results: Serum levels of creatinine and urea and urine output during the first three days after the operation did not differ statistically significantly between two groups (P = .549, P = .306 and P = .375, respectively). Early kidney function was better significantly in group 1 (5.3 ± 3.2 versus 8.6 ± 8.0 hours; P = .048). Conclusion: Premedication of the kidney transplant donors with low-dose dopamine accelerates early kidney function after transplantation, but has no effect on the hemodynamic status and serum levels of creatinine and urea in the donors.